2022
DOI: 10.3389/fpsyt.2022.1026625
|View full text |Cite
|
Sign up to set email alerts
|

The association between violent video game exposure and sub-types of school bullying in Chinese adolescents

Abstract: BackgroundSchool bullying among adolescents has been a worldwide public health issue. It has been observed that adolescents who are exposed to violent video games (VVGs) are often more aggressive. However, research on the association between violent video game exposure (VVGE) and different types of school bullying is limited in the Chinese context.ObjectiveThe purpose of this study was to explore whether VVGE is linked to school bullying behaviors among Chinese adolescents and to examine the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Currently, various studies have indicated the consequences of internet addiction on cyberbullying victimization [58] as well as other forms of bullying victimization in Lebanese adolescents [32], Hungarian adolescents [33] and Chinese adolescents [59]. As association does not equal causation, whether internet addiction disrupts their participation in social networks thereby making these adolescents more vulnerable to be bullied, or whether these adolescents have personalities that make them more likely to play video games and are more likely to be bullied, could all become testable hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various studies have indicated the consequences of internet addiction on cyberbullying victimization [58] as well as other forms of bullying victimization in Lebanese adolescents [32], Hungarian adolescents [33] and Chinese adolescents [59]. As association does not equal causation, whether internet addiction disrupts their participation in social networks thereby making these adolescents more vulnerable to be bullied, or whether these adolescents have personalities that make them more likely to play video games and are more likely to be bullied, could all become testable hypotheses.…”
Section: Discussionmentioning
confidence: 99%